Investigation of recycling repetition effect on deinkability efficiency and printing properties - SÖNMEZ, SİNAN (TAYLOR & FRANCIS LTD, 2022)
The primary aim of this study is to determine the effectiveness of separating ink particles which are adherent to cellulose fibers from cellulose fibers after recycling. In addition, after recycling, physical and optical changes in cellulose fibers are observed and inkjet and laserjet printing properties are investigated in some parameters. Initially, the reference papers are recycled according to the 11p standard. After this stage, the pulps are subjected to double stage bleaching (0.4% FAS + H2O2). Then, color scales are printed with inkjet and laserjet printers, and color measurements are made with X-Rite Exact spectrophotometer. These papers are again recycled according to the INGEDE 11p standard. As a result of the calculations, it is observed that there is an accurate ratio between the number of recyclings and the detachability of ink particles from cellulose fibers. In addition, it is determined that the resistance properties of the papers subjected to the second recycling stage are weakened and the porosity increased according to the obtained data. After the second recycling stage, it is determined that the cellulose peak values obtained in the FTIR spectrum became more pronounced and the results overlapped when compared with the ERIC values. In the SEM images, it can be said that after the second recycling stage, the fringing of the fibers increases with hornification and the fiber surface area began to expand.
Keywords: Recycling; inkjet; laserjet; CMYK; deinking; BACTERIAL CELLULOSE; INK; ROUGHNESS; DEINKING; ENERGY; FIBER